The Quantico Files: Dead Fall - Book 2 - Mehl, Nancy (Minneapolis, MN : Bethany House Publishers, a division of Baker Publishing Group, 2021)
"When a renowned profiler is found dead in his hotel room and it becomes clear the killer is targeting agents in Alex Donovan's unit, she is called to work on the strangest case she's ever faced. Things get personal when the brilliant killer strikes close to home, and Alex will do anything to find the killer-even at the risk of her own life"--
Keywords: United States. -- Federal Bureau of Investigation -- Fiction; Criminal profilers -- Fiction; Serial murder investigation -- Fiction; Religious fiction; Detective and mystery fiction; Thrillers (Fiction)